Gambaran Stres Kerja Petugas Pendaftaran Rawat Jalan di RSUP Dr. Sardjito Yogyakarta - Risma Dwi Ambarwati; Gamasiano Alfiansyah; Sustin Farlinda; Sugeng Sugeng (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Occupational stress is recognized as a global health issue that affects all professions, no other profession inthe health field i.e. medical record registration section. RSUP Dr. Sardjito Yogyakarta has a total data visitannually on an outpatient registration, which is in 2018 as much as 469813 and in 2019 as many as 518806.The number of visits explained at least the registration staff should serve 200-300 patients every day. Knownerrors that occur in SIMETRISS also harm the officer because inevitably officers should double job. TheStress of work felt by the officers of the list is often felt muscle tension, feel tension, fast anger, feel anxiety,and difficulty concentrating in the work. Stressful work if not resolved will have an impact on activities in thescope or out of work. The research aimed to figure out the work stress overview of the registration officers inRSUP Dr. Sardjito Yogyakarta. The collection methods used are interviews. The analysis of the data used inthis study was qualitative. The results of the study showed work stress experienced by outpatient registrationofficers, that is caused by a physical work environment that was less comfortable so later would cause a lackof concentration by the officers and the declining of officers performance; the conflict between family demandsand the institution demands such as the lack of break time and the presence of a sustained shift; performancedemands to work quickly and precisely however the support facilities, Simetriss, which was still error alsoraised the pressure for the worker. RSUP Dr. Sardjito Yogyakarta has reduced some problems by conductingeffective consultation on outpatient registration officers.